THE EFFECT OF ANTERIOR CRUCIATE HEALING ON THE UNINJURED LIGAMENT INSERTION SITE - Haus, BM (2011)
PURPOSE: Changes in the insertion site of the ACL after enhanced suture repair with collagen-platelet-composites (CPC) have not yet been defined. In this study, we hypothesized that fibroblasts and osteoclasts would participate in generating histologic changes in insertion site morphology after transection and bioenhanced repair of the ACL, and that these changes would be age-dependent. METHODS: Skeletally immature, adolescent, and adult Yucatan mini-pigs underwent ACL transection and bioenhanced suture repair. The histologic response to repair of the insertion site was evaluated at 1, 2, 4 and 15 weeks. RESULTS: In young and adolescent animals treated with bioenhanced suture repair with CPC, changes in the insertion site included: (1) fibroblastic proliferation with loss and return of collagen alignment in the fibrous zone; (2) osteoclastic resorption within fibrocartilage zones at 2–4 weeks; and (3) partial reappearance of fibrocartilage zones at 15 weeks. In adult animals; however, degenerative changes were noted by 15 weeks: (1) loss of parallel arrangement of collagen fibers in the fibrous zone; and (2) increasing disorganization and loss of columnation of chondrocytes in the fibrocartilage zone. CONCLUSIONS: These results suggest that fibroblasts and osteoclasts mediate histologic changes at the insertion site during bioenhanced suture repair of the ACL which may prevent insertion site degeneration, and that the magnitude of these changes may be a function of skeletal maturity.